Non-enzymatic oxylipin production in a mudflat microphytobenthic biofilm: evidence of a diatom response to light - Doose, Caroline; Oger, Camille; Mas-Normand, Lindsay; Durand, Thierry; Hubas, Cédric (Frontiers in Photobiology, 2024)
Microphytobenthos (MPB) is a diatom dominated microbial community of primary producers inhabiting the mudflat sediments. On one hand, the benthic diatoms display photo-protective strategies to face extreme light variations susceptible to generate cellular oxidative stress. On the other hand, oxidative stress induces the production of reactive oxygen species (ROS) that generate oxylipins, oxygenated metabolites of polyunsaturated fatty acids (PUFAs), which are among the known chemical mediators in diatoms. However, non-enzymatically generated oxylipins known as isoprostanoids or isofuranoids are poorly studied in diatoms. To better understand the roles of the latter in migrational MPB light response, we investigated the effect of different irradiances corresponding to dark (D), low light (LL, 50 and 100 µmol. photons. m−2. s−1PAR), medium light (ML, 250 µmol. photons. m−2. s−1 PAR), high light (HL, 500, 750 and 1000 µmol. photons. m−2. s−1PAR), on the isoprostanoids production by the biofilm’s organisms. The PUFAs precursors of the varying oxylipins evidenced a diatoms response to irradiance. Under 1000 PAR condition, the total amount of isoprotanoids increased, indicating an oxidative stress response. Isoprostanes (IsoPs) and prostaglandins (PGs) characterized the HL conditions and evidenced lipid peroxidation probably linked to the higher generation of ROS by the photosynthesis. On the contrary, the phytoprostanes (PhytoPs) characterized the LL and ML, where the ROS scavengers were probably not overwhelmed. This first investigation of non-enzymatic oxylipin production by a microphytobenthic biofilm under different irradiances highlighted the interest to explore their potential signaling roles related to MPB light responses.